Hubungan Dukungan Orang Tua dengan Hasil Belajar Siswa pada Pembelajaran IPS Kelas V di SD Negeri 01 Sri Basuki Way Kanan Tahun2021/2022 - Mustofia Ningrum, Anim; Rahma Pratiwi , Emy Yunita (Prodi Pendidikan Guru Sekolah Dasar, 2024)
In social studies learning at the basic education level such as elementary school (SD), good social interaction and mutual support between parents and children are needed. However, there are still many parents who do not provide support or tutoring for their children so that their children do not get proper learning outcomes as expected. This study aims to determine the relationship between parental support and student learning outcomes in Social Studies learning in Class V at SD Negeri 01 Sri Basuki Way Kanan. This type of research is correlational research with quantitative methods. The sample in this study amounted to 40 fifth grade students of SD Negeri 01 Sri Basuki in the 2021/2022 academic year. The instruments in this study were questionnaires and documentation. Data collection techniques using questionnaires and documentation. The data analysis technique uses the